The impact of memorable umrah and hajj experienceson the subjective well-being on pilgrims in malaysia - Nur Athirah Hazman; Nur Athirah Hussaini; Nur Athirah Mohamad Nordin; Nur Atiqah Amran (2023)
This study was proposing to examine the impact of memorable umrah and hajj experiences on the subjective well-being of pilgrims in Malaysia. The independent variable of this study consists the knowledge, refreshment, local culture, and meaningfulness. Next, this study has three objectives to examine the relationship between knowledge and visitor subjective well-being among umrah and hajj pilgrims, to examine the relationship between refreshment and visitor subjective well-being among umrah and hajj pilgrims, examine the relationship between meaningful and visitor subjective well- being among umrah and hajj pilgrims, and to examine the relationship between local culture and visitors’ subjective well among umrah and hajj pilgrims. This study is believed to provide notable insights to the host country, tour operator and travel agent in organizing memorable experiences umrah and hajj. Keyword: Umrah, Hajj, Memorable Tourism Experience and subjective well-being.